2019
DOI: 10.3390/su11195252
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Differentiated Impact Mechanism of Parent Company Shareholding and Managerial Ownership on Subsidiary Responsive Innovation: Empirical Analysis Based on ‘Principal–Agent’ Framework

Abstract: Under the dynamic competition situation, the innovation competition interaction between enterprises will take the form of mutual responding, while the formulation and implementation of responsive innovation strategy will be influenced by both shareholders and managers in the principal–agent relationship. In our research, we try to understand how the difference of governance logic between shareholders and managers affects innovation interaction strategy of enterprises. In order to achieve this research goal, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…(2) The discussion on improving the technological innovation path of the subsidiaries within the group is insufficient. The parent shareholding has a negative impact on subsidiary' responsive innovation of subsidiary, while the subsidiary with more managerial ownership choose relatively positive responsive innovation [8].…”
Section: Ferraris Et Al 2017 By Analyzing the Influencing Factors And...mentioning
confidence: 97%
“…(2) The discussion on improving the technological innovation path of the subsidiaries within the group is insufficient. The parent shareholding has a negative impact on subsidiary' responsive innovation of subsidiary, while the subsidiary with more managerial ownership choose relatively positive responsive innovation [8].…”
Section: Ferraris Et Al 2017 By Analyzing the Influencing Factors And...mentioning
confidence: 97%
“…Using Chinese listed companies, including Shanghai and Shenzhen’s main boards and small and medium-sized boards, and the Growth Enterprise Board, researchers compared corporate performance with equity incentive plans and without equity incentive plans, and they found that the former was better than the latter [ 34 ]. Similarly, researchers focused on listed companies in Shanghai and Shenzhen from 2007 to 2016 and showed that the more managers held the share percentage, the more likely they were to engage in positive strategic response innovation, which may enhance companies’ sustainable development capacity [ 35 ]. As a normal corporate governance mechanism, equity incentives usually play an important role in preventing or reducing managers’ immoral behavior and attracting and retaining talent [ 36 , 37 ], and they can help to mitigate agency conflicts and promote corporate performance [ 10 ].…”
Section: Research Hypothesesmentioning
confidence: 99%
“…In this study, it is believed that the parent-subsidiary corporations executives' ties can strengthen the role of scholar-type CEOs in promoting industrial AI transformation through a synergy mechanism. The specific logic is as follows: First, as an important manifestation of strengthening the power allocation of subsidiary executives, the parent-subsidiary corporations executives' ties has a positive effect on stimulating missionalism and stewardship mentality of subsidiary CEOs (Belenzon et al, 2019;Xu et al, 2019). Scholar-type CEOs can more effectively avoid adverse selection and moral hazard problems by correcting short-sighted behavior and are better able to give full play to their innovative thinking mode to effectively capture the signals of policy changes and gain insight into the future prospects of AI applications, and then more funds will be invested in long-term industrial AI transformation projects (Sheng et al, 2022).…”
Section: 3mentioning
confidence: 99%